Job Demands, Working Postures, Workstations, and Prevalence of Workrelated Musculoskeletal Disorders Among Teachers in Silliman University - Ramos, Reynaldo D.; Putong, Cyflor E. (Silliman Journal, 2022)
This paper aims to establish the magnitude of work-related musculoskeletal disorders (WMSDs) among 119 randomly selected teachers in Silliman University and to point out the associated risk factors by examining the job demands, workstation and the working postures assumed by teachers as they performed their assigned tasks. The results of the study showed that the conduct of lectures, test preparation, and computer work consumed majority of the teacher’s time. The three-month prevalence of musculoskeletal disorders was 82% and majority experienced shoulder pain, lower back pain, upper back pain, and neck pain. The posture analysis showed that neutral postures were observed in the back, arms, and legs except in the neck where combined non-neutral posture is about 59%. Major ergonomic deficiencies were found in the backrest, seat pan, arm rests, seat and work surface heights. Worth noting to both seated and standing workstations is that none of these were adjustable to accommodate the varied tasks of teaching. Therefore, the teachers in the study were at risk to work-related musculoskeletal disorder because the nature of their work demanded them to assume a variety of postures and activities that may be perpetuated by an improperly designed workstation.